Penghindaran Pajak Dari Sudut Pandang Aset Yang Dimiliki Perusahaan - Lasmarina Suci Oktavia; Nera Marinda Machdar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Tax avoidance is a company strategy to minimize the tax burden. Management of inventory intensity, liquidity and intangible assets can be an important factor in determining company policies regarding tax avoidance. This research aims to determine and analyze the influence of inventory intensity, liquidity and intangible assets on tax avoidance, and knowing and analyzing transfer prices as a moderating variable can strengthen the relationship between inventory intensity, liquidity and intangible assets on tax avoidance. This research applies a causal research method using a quantitative approach through the literature review method. The population used in this research is energy sector companies listed on the Indonesia Stock Exchange during the 2019-2024 period. Sampling in this research used purposive sampling with predetermined criteria. The type of data in this research is secondary data in the form of annual reports. This research uses multiple linear regression analysis methods and moderated regression analysis. The research results show that inventory intensity has a negative effect on tax avoidance, liquidity has a positive effect on tax avoidance, intangible assets have a positive effect on tax avoidance, and transfer prices can strengthen the relationship between inventory intensity, liquidity and intangible assets on tax avoidance. Future research is expected to include other variables to expand the research analysis